Pengaruh Kualitas Pelayanan Dan Perceived Value Terhadap Kepuasan Pelanggan Melalui Customer Trust Di The Margo Hotel Depok - Sahri, Mawarda; Sukma, Rivera Pantro (Innovative: Journal Of Social Science Research, 2024)
To create excellence in the hotel industry, companies must prioritize service quality and customer value to gain trust so that customers or hotel guests feel satisfied. Trust is the result of an action to a customer that produces a positive reaction for the company and does not have the potential to produce a negative impact (Anderson & Narus, 1990). Customer satisfaction is when customers feel their expectations are met when buying and experiencing products and services from the company directly (Mohsan et al., 2011). The purpose of this study is to find out how the influence of customer value and service quality on customer satisfaction and trust at Hotel Margo. All participants in this study were customers of Margo Hotel. In this study, 200 participants were collected through the use of questionnaires and Purposive Sampling methods. Structural Equation Modeling (SEM) is used in the process of data analysis with the help of Smart-PLS software. The findings of this study show that customer value and service quality have a considerable impact on customer trust and satisfaction. The results showed that customer value has a direct positive and significant influence on customer satisfaction and trust, and service quality has a direct positive and significant influence on these two variables.